2017
DOI: 10.15171/bi.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Drug nanocarrier agents based on starch-g-amino acids

Abstract: Introduction: In the recent decades, starch has been modified using different methods for the various forms of applications. Some new starch derivatives were prepared through a simple and convenient method in the grafting of amino acids: L-alanine, L-leucine and L-phenyl alanine to starch. Methods: First, the amine groups of amino acids were protected using phthalic anhydride then the acidic side of amino acids were activated with chlorination using thionyl chloride, and the resultant acid chlorides were reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In contrast to previous studies focusing on the generation of cationic starch derivatives such as starch methylene dimethylamine, starch amino acid conjugates, or starch exhibiting quaternary ammonium substructures, the cationic starch described in this study is, to our knowledge, the first exhibiting vicinal amino groups as ligands.…”
Section: Resultsmentioning
confidence: 84%
“…In contrast to previous studies focusing on the generation of cationic starch derivatives such as starch methylene dimethylamine, starch amino acid conjugates, or starch exhibiting quaternary ammonium substructures, the cationic starch described in this study is, to our knowledge, the first exhibiting vicinal amino groups as ligands.…”
Section: Resultsmentioning
confidence: 84%
“…Characteristic functional groups were observed, which represents the polysaccharide groups Fig. 1 [25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Up to now, CAPs have shown promising applications in tissue regeneration, tumor therapy, drug/gene delivery, and bioimaging. [26][27][28] Recent studies in our group have found that citrate-based polymer poly(citric acidpolyethylene glycol) (PCG) have the ability to regulate macrophage subtypes and inhibit inflammation. 29 However, it is unknown whether this polycitrate-based polymer can promote diabetic wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Citric acid is a natural organic metabolite, and the citric acid‐based polymers (CAPs) have shown good biocompatibility, biodegradability, and modifiability of mechanical properties 25,26 . Up to now, CAPs have shown promising applications in tissue regeneration, tumor therapy, drug/gene delivery, and bioimaging 26–28 . Recent studies in our group have found that citrate‐based polymer poly(citric acid‐polyethylene glycol) (PCG) have the ability to regulate macrophage subtypes and inhibit inflammation 29 .…”
Section: Introductionmentioning
confidence: 99%